PENERAPAN METODE KERJA KELOMPOK DALAM PEMBELAJARAN SENI TARI PADA SISWA KELAS XI RPL 2 SMKN 1 PANYINGKIRAN - Mudiawati, Mumun (2013)
This Research title is " Applying Team-Work method in study of art dance a class student XI RPL 2 SMKN I PanyingkiranMajalengka". This research of background by ability of cooperation, lack of communications between friend, passive student attitude to study because done by study method more at individual duty. This research is conducted for try applying of team-work method in study of dance art. This research answer the formula of problem of as follows: (1) ability of student in working along, communicate and each other esteeming [at] study of art dance before applied by theX the team-work method; (2) how is process applying of team-work method in study of dance art (3) how do result applying of team-work method at study of art dance in the effort improving ability work along, communicate and each other esteeming. This research aim to to know (1) ability of student in working along, communicate and each other esteeming [at] study of art dance before applied by theX the team-work method; (2) process applying of team-work method in study of dance art ; (3) result of applying of team-work method in improving ability work along, communicate and each other esteeming at study of dance art.The method used in this research is sham experiment method with desaintesawal-tes final of single group ( the one group pretest posttest) what is done at research population member, that is class XI RPL in SMKN I PanyingkiranMajalengka, school year of 2012/2013 with sampel research of class XI RPL 2 as experiment class. In this research, the class is given tes before and after getting treatment. used by theX instrument of this research is tespraktik. Pursuant to data processing result, this research use the hypothesis test that is uji-t with level signifikanα= 0,05. After done by the examination of hypothesis, have been known that value t-count bigger than at value t-tables that is 25, 76 > 2, 035. That there are the difference is very big in study of art dance before and after applying the team-work method. Mean, storey;level study of class student XI RPL 2 SMKN I Panyingkiran show the difference signifikan. Pursuant to the mentioned hence acceptable raised hypothesis, that is applying of team-work method in study of dance art can improve ability of student in working along, communicate and each other esteeming.